Study on Damage Characteristics and Physical Field Characteristics of Roadway Surrounding Rock Under Multiple Disturbances - Jiuxin Zhang; Hongyan Qin; Zhenhua Ouyang; Ningbo Zhang; Yiyan Zhang; Yang Liu; Wenshuai Li; Ranran Zhou (Energy Science & Engineering)
ABSTRACT During the mining process, repetitive stress disturbances induced by mining activities can lead to alterations in the physical properties of coal, potentially resulting in rockburst occurrences within tunnels. To investigate the propagation rule of physical field characteristics and characteristics of failure in roadway surrounding rock under multiple disturbance damage caused by dynamic load, a combined experimental and theoretical analysis is conducted to study the weakening effect of rock mass under various disturbance circumstances. A model of roadway surrounding rock loosening and failure under multiple disturbances was proposed. The degree of damage is quantified by defining the weakening coefficient Di, A “weakening variable method” is proposed to confirm the main parameters of the Holmquist‐John‐son‐Cook (HJC) model under different disturbance conditions. The reliability of these findings was validated through a microseismic event at the Tangshan coal mine's 0250 working face in 2020, followed by numerical simulation studies. The results indicate that damaged coal weakens the intensity of stress waves at the same source velocity, with the strongest effect observed at interfaces between different damage zones. Furthermore, damaged coal exhibits a stronger weakening effect on stress wave propagation speed compared to undamaged coal in non‐interface areas. The study on roadway stability reveals that severely damaged coal‐rock samples significantly weaken stress waves; however, they also exhibit lower minimum energy for dynamic failure in roadway surrounding rock, indicating that low‐stress waves cause greater damage under severe damage conditions. The study investigates the impact of coal rock mass degradation on the stability of surrounding roadways under various disturbance conditions, which holds significant implications for the timely identification of potential instability risks in damaged coal bodies, optimization of support strategies, and ensuring mining safety.